Outcome after surgical treatment of dermatofibrosarcoma protuberans: Is clinical follow‐up always indicated?. Issue 5 (15th January 2019) - Huis in 't Veld, Eva A.; van Coevorden, Frits; Grünhagen, Dirk J.; Smith, Myles J.; van Akkooi, Alexander C. J.; Wouters, Michel W. J. M.; Hayes, Andrew J.; Verhoef, Cornelis; Strauss, Dirk C.; van Houdt, Winan J.
Abstract : Background: Dermatofibrosarcoma protuberans (DFSP) is a rare soft tissue sarcoma for which clinical examination up to 10 years is recommended. The objective of this study was to identify prognostic factors for recurrences and metastases that can be used to evaluate the validity of follow‐up schedules after treatment for DFSP. Methods: Patients with DFSP who received treatment between 1991 and 2016 at 3 tertiary centers were included. Cox regression analyses were conducted to identify variables associated with the primary endpoints. Results: In total 357 patients were included, with a median age of 38 years (age range, 2‐87 years) and a median follow‐up of 60 months (interquartile range, 24‐115 months). Eighty‐one patients developed recurrent disease (22.7%), and the median time to recurrence was 55.5 months (interquartile range, 20‐90 months). Of these, 50 tumors (61.7%) were identified by patient self‐examination, whereas 3 recurrences (3.7%) were identified at clinical surveillance. For the remaining 28 tumors, no information was available on how the recurrences were identified (34.6%). Fibrosarcomatous change (hazard ratio, 21.865; P  < .001), and positive resection margins (hazard ratio, 14.645; P  < .001), were independent prognostic factors for recurrence. Metastases occurred in 4 patients (1.1%). All tumors were identified by imaging after patients presented with symptomatic metastases. Fibrosarcomatous change ( P  < .001) and tumor size >5 cm ( P  = .014) were associated with the development of metastases. Conclusions: Disease recurrence after resection of DFSP remains a significant issue, whereas metastases are uncommon. The majority of recurrences are identified by patient self‐examination. Consideration should be given to individualized follow‐up schedules based on risk factors for recurrences and metastases. Abstract : Local recurrence after resection of dermatofibrosarcoma protuberans remains a significant issue, and most recurrences are identified by patient self‐examination. Metastases are uncommon, and all in this study were identified by imaging after patients presented with symptomatic metastases.